Improving Lecturersâ Performance through Effective Learning at Department of Islamic Education at Faculty of Islamic Education and Teacher Training IAIN IB Padang - Trinova, Zulvia (AT-TALIM, 2015)
The aim of this study is to describe the work situation variables, achievement motivation on the performance of Islamic education (PAI) lecturer in creating effective learning in the Department of PAI. This study is a combination of quantitative and qualitative methodss (mixed methods) obtained from observation, questionnaire, interviews, and documentation. The data were analyzed through statistics. Qualitative data were analyzed by using data reduction, categorization, and data verification and conclusions. The working athmosphere contributes 48.7% to the influence on the lecturer performance work and the motivation contributes 43.0% to the impact on the lecturer performance. Work situation and achievement motivation respectively affect the work performance of 58.3%. Learning approach used is expository approach, the inquiry, and emotional approach. It was also used PAKEM approach and an approach that is Andragogy. The learning method applied in this research is multi method in the form of active active learning. PAI lecturers used printed media, dicussion paper, and electronic media. Keywords: Effective learning, PAI, performance.Copyright © 2015 by Al-Talim All right reserved